Climate change mitigation targets set by global firms: Overview and implications for renewable energy. (October 2018) - Wang, Derek D.; Sueyoshi, Toshiyuki
Abstract: Global firms are increasingly adopting greenhouse gas mitigation targets in response to climate change. These targets serve as a spur for carbon mitigation initiatives, provide guidelines to select appropriate mitigation actions, and set the standards to measure the progress of the mitigation efforts. Despite their important functionalities, firm-level mitigation targets have rarely been studied. In this paper we aim to provide a comparative view on mitigation targets set by global firms across different countries and industrial sectors. The analysis focuses on four dimensions, i.e., adoption, metric, scope, and stringency. We find Japan far leads the other major countries in terms of target adoption, but the targets of Japanese firms are generally less stringent. Canadian firms are laggards in both target adoption and target stringency. The mitigation targets are also considerably uncommon among Australian firms. Firms in developing countries fall behind in target stringency and display a significantly greater divergence than developed countries in sectoral adoption rate. The European Union firms are most likely to cover the emissions in their supply chains in targets. Target stringency has substantially tightened from 2005 to 2012. For all the countries in this study, around 95% of the firm-level targets are more stringent than the Intended Nationally Determined Contributions submitted to the Paris Agreement. Setting mitigation target has a significant positive impact on both the likelihood of investing in renewable energy and the amount of investment in renewable energy. However, there is no evidence that more stringent targets lead to higher investment. These findings point to the most pressing issues with regard to corporate mitigation target-setting that policymakers and corporate management should address. Highlights: Firm-level GHG mitigation targets play a critical role in tackling climate change. The link between mitigation targets and renewable energy is analyzed. Targets set by global firms in different countries and sectors are studied. The findings bear implications for renewable energy and climate policies.